Physical health effects of sedentary behaviour on adults with an intellectual disability: A scoping review - Lynch, Louise Annmarie; Lynch, Louise (Journal of Intellectual Disabilities, 2022)
This literature review was designed to establish the effects of sedentary behaviour on the physical health of adults with an intellectual disability. Sedentary behaviour is defined as any waking behaviour characterized by an energy expenditure of ≤1.5 METs while in a sitting, lying or reclining posture. An extensive search was executed in six databases: EMBASE, Medline, CINAHL, PsycINFO, ASSIA and Web of Science. Following screening, 18 articles remained for inclusion in the review. A thematic analysis using the Braun and Clarke six step process resulted in the identification of seven broad health areas. Studies showed a prevalence of obesity, multimorbidity and metabolic syndrome as well as elevated levels of sedentary behaviour in adults with an intellectual disability. This literature review demonstrated that sedentary behaviour could be a contributor to the poor health which is common in adults with an intellectual disability. However to date the body of evidence does not confirm a cause-and-effect relationship.
Keywords: Sedentary behaviour, health, intellectual disability; adults; Ageing; Cancer; Chronic Illness self-management; Health attitudes and behaviour; Health outcomes; Health status and inequalities; INTELLECTUAL DISABILITIES; Intellectual Disability; Nurse Education; OLDER PEOPLE; Age-related disability; Autistic Spectrum disorders; Intellectual Disability